2016
DOI: 10.1177/1468087415609855
|View full text |Cite
|
Sign up to set email alerts
|

Scalable turbocharger performance maps for dynamic state-based engine models

Abstract: Adapting turbocharger performance maps to a form suitable for dynamic simulations is challenging for the following reasons: (1) the amount of available data is typically limited, (2) data are typically not provided for the entire operating range of the compressor and turbine and (3) the performance data are non-linear. To overcome these challenges, curve fits are typically generated using the performance data individually for each device. The process, however, can take uneconomical amounts of effort to impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, finding the most suitable compressor/turbine for a given application is a hard task, and the most efficient selection is not ensured. In this way, the approach developed by Bell and coworkers [13] is adopted in this study. Essentially, a dimensional analysis technique is employed to generate a suitable map once (generic, non-dimensional), and then adapt the map for use in simulation across a range of sizes.…”
Section: Methods To Implement Non-dimensional Performance Maps -Scalabmentioning
confidence: 99%
“…However, finding the most suitable compressor/turbine for a given application is a hard task, and the most efficient selection is not ensured. In this way, the approach developed by Bell and coworkers [13] is adopted in this study. Essentially, a dimensional analysis technique is employed to generate a suitable map once (generic, non-dimensional), and then adapt the map for use in simulation across a range of sizes.…”
Section: Methods To Implement Non-dimensional Performance Maps -Scalabmentioning
confidence: 99%
“…The compressors that were used in this study were derived from an Aeristech electric supercharger, which is able to reach a pressure ratio of 2.8 [15]. The experimental data that were used were adapted to this configuration by applying a reliable scaling method to adapt the compressor and the turbine to the size of the stack and the requirement of air mass flow [16][17][18].…”
Section: Compressor and Turbine Scaling Methodsmentioning
confidence: 99%
“…Even with the scaling laws simplified, matching a turbocharger to an engine is a far more difficult task in itself, as the turbomachinery diameter is not chosen but needs to be obtained to provide the desired performance, and this task needs to be accomplished simultaneously for both compressor and turbine. Bell et al [15] showed good results for scaling process by first identifying the compressor diameter and the torque required from the turbine to reach the necessary boost, yielding good turbocharger performance results at various engine sizes. However, the author does not show whether the results were matched to specific engine performances.…”
Section: Turbocharging Map Scalingmentioning
confidence: 99%
“…However, most methods investigated have not considered scaling the efficiency, which leads to the questions, should the efficiency be scaled, or is it acceptable to assume the change as negligible to the final results? The efficiency can be established as a function of the corrected shaft speed and the pressure ratio as shown in Equation (3) [15].…”
Section: Turbocharging Map Scalingmentioning
confidence: 99%
See 1 more Smart Citation